(untitled) (Jahangirnagar University Journal of Biological Sciences, 2017)
Alpha amylases (?-amylases) are one of the most imperative enzymes for producing simple sugar units from complex sugar molecules. Attempts were made to isolate amylolytic bacterial strains from soil samples of tannery wastes collected from Hazaribagh, Dhaka and subsequent partial characterization was performed. Bacterial isolates were primarily screened for ?- amylase activity on starch agar medium. Based on microscopic and biochemical properties of isolates, ?-amylase activity of bacterial isolates were determined to find out two best producers of the enzyme. Subsequent molecular identification of these two ?-amylase producing bacterial isolates using 16s rRNA sequence analysis showed that isolates were Bacillus amyloliquefaciens and B. subtilis respectively. In submerged fermentation the B. amyloliquefaciens showed the highest activity (2.13 U/ml) while B. subtilis showed the second highest activity (1.89 U/ml). Characterization of the enzyme produced by B. amyloliquefaciens revealed that the maximum activity demonstrated at incubation time 25 min, pH 7.0 and temperature 500C. This newly isolated B. amyloliquefaciens could be exploited for the industrial production of ?-amylase with commercial implications. Jahangirnagar University J. Biol. Sci. 5(2): 1-10, 2016 (December)